Smart vacuum cleaner using fuzzy logic / Ismalily Ismail - Ismail, Ismalily (2008)
Fuzzy control method and algorithms, including many specialized software and hardware available on the market, may be classified as one type of intelligent control. This is because fuzzy system modeling, analysis and control incorporate a certain amount of human knowledge into its component such as fuzzy sets, fuzzy logic, and fuzzy rule bases. This thesis deals with the modeling of the vacuum cleaner using fuzzy logic controller by using MATLAB and Simulink software. In this thesis, the model of the smart vacuum cleaner Fuzzy Logic Controller (FLC) is developed by using Matlab Fuzzy Logic Toolbox and Simulink. The FLC designed in this project has two inputs and one output where the first input is the types of surface and the second input is the types of dirt or dirt condition on the surface. The output of this FLC is the suction power where this output signal will be used as the voltage supplied to the suction motor. Four shapes of membership function will be tested and the shape that can produce a good result due to the output signal and time response will be used in the FLC. The result of this FLC is the output signals that were produced by the controller will give the output value based on the inputs implemented to the FLC.